Lupus risk variants in the PXK locus alter B-cell receptor internalization - Vaughn, Samuel E.; Foley, Corinne; Lu, Xiaoming; Patel, Zubin H.; Zoller, Erin E.; Magnusen, Albert F.; Williams, Adrienne H.; Ziegler, Julie T.; Comeau, Mary E.; Marion, Miranda C.; Glenn, Stuart B.; Adler, Adam; et al. (Frontiers in Genetics, 2015)
Genome wide association studies have identified variants in PXK that confer risk for humoral autoimmune diseases, including systemic lupus erythematosus (SLE) or lupus, rheumatoid arthritis and more recently systemic sclerosis. While PXK is involved in trafficking of epidermal growth factor Receptor (EGFR) in COS-7 cells, mechanisms linking PXK to lupus pathophysiology have remained undefined. In an effort to uncover the mechanism at this locus that increases lupus-risk, we undertook a fine-mapping analysis in a large multi-ancestral study of lupus patients and controls. We define a large (257kb) common haplotype that confers lupus risk detected only in European ancestral populations and spans the promoter through the 3’ UTR of PXK. The strongest association was found at rs6445972 with P < 4.62 x 10-10, OR 0.81 (0.75 – 0.86). Using stepwise logistic regression analysis, we demonstrate that one signal drives the genetic association in the region. Bayesian analysis confirms our results, identifying a 95% credible set consisting of 172 variants spanning 200kb. Functionally, we found that PXK operates on the B-cell antigen receptor (BCR); we confirmed that PXK influenced the rate of BCR internalization. Furthermore, we demonstrate that individuals carrying the risk haplotype exhibited a decreased rate of BCR internalization, a process known to impact B cell survival and cell fate. Taken together, these data define a new candidate mechanism for the genetic association of variants around PXK with lupus risk and highlight the regulation of intracellular trafficking as a genetically regulated pathway mediating human autoimmunity.